Compact tripple U-shaped slot loaded circular disk patch antenna for bluetooth and WLAN application - Ansari J.A.; Mishra A.; Yadav N.P.; Singh P.; Vishvakarma B.R. (My University, 2025)
In the present paper a three U-shaped slot loaded disk patch antenna is analysed by using circuit theory concept. The antenna shows dual resonance. The resonance frequency of single layer patch is found to be 1.84 GHz and 2.61 GHz (simulated 1.80 GHz and 2.61 GHz) whereas for two layers dielectric antenna, it is 2.21 GHz and 3.14 GHz (simulated 2.20 GHz and 3.13GHz) respectively. The frequency ratio is found to be 1.41 (simulated 1.45) for single layer patch antenna and 1.42 (simulated 1.42) for two dielectric layers patch antenna. The bandwidth of single layer patch antenna is found to be 1.52% and 1.68 % for lower and upper resonance frequency respectively while for two layers dielectric antenna it is 1.10 % and 1.53 %. Introducing three U-slot in the circular disk 16.54 % of size reduction has been achieved. The theoretical results are compared with the simulated results obtained from IE3D which are in close agreement. © 2011 ISRAMT.